"Change Really Does Need to Start From Home": Impact of an Intimate Partner Violence Prevention Strategy Among Married Couples in Nepal. Issue 15 (August 2021) - McGhee, Susi; Shrestha, Binita; Ferguson, Gemma; Shrestha, Prabin Nanicha; Bergenfeld, Irina; Clark, Cari Jo
Approximately 54% of women in rural Nepal report lifetime physical or sexual violence. The Change Starts at Home project is a primary prevention strategy to reduce and prevent marital intimate partner violence (IPV). This study analyzed in-depth interviews with 17 married couples ( n = 34 individuals) at intervention midline and end line. Case-based analysis and thematic summaries were used to assess change, couple concordance, and gendered reporting patterns at midline. Individual changes included husband's alcohol use and roaming tendencies. Relationship-level changes comprised labor roles, communication, decision making, conflict resolution, and experience of IPV. End line interviews were analyzed to understand sustenance of change within these same individual and relationship dynamics. Results indicate promising shifts in men's individual behavior and marital dynamics, which underpin IPV risk.